An Analysis of Idiomatic Expression Presented in the New Songs of the Album Positions by Ariana Grande - Roger, Jocelynne Victoria; Ariyaningsih, Ni Nyoman Deni (English Department, Faculty of Humanities, Andalas University, 2023)
The idiomatic expressions is a common phenomenon in language use as a communication tool between humans. The use of idiomatic expressions can be presented in the dialogue and expressed in a literary work, such as in a song. It led the researcher to study further 1) the types of idiomatic expressions and 2) the meanings presented in the idiomatic expressions of 6 songs in